Effective treatment options for musculoskeletal pain in primary care: A systematic overview of current evidence. - Opeyemi O Babatunde; Joanne L Jordan; Danielle A Van der Windt; Jonathan C Hill; Nadine E Foster; Joanne Protheroe (PLoS ONE)
Background & aims Musculoskeletal pain, the most common cause of disability globally, is most frequently managed in primary care. People with musculoskeletal pain in different body regions share similar characteristics, prognosis, and may respond to similar treatments. This overview aims to summarise current best evidence on currently available treatment options for the five most common musculoskeletal pain presentations (back, neck, shoulder, knee and multi-site pain) in primary care. Methods A systematic search was conducted. Initial searches identified clinical guidelines, clinical pathways and systematic reviews. Additional searches found recently published trials and those addressing gaps in the evidence base. Data on study populations, interventions, and outcomes of intervention on pain and function were extracted. Quality of systematic reviews was assessed using AMSTAR, and strength of evidence rated using a modified GRADE approach. Results Moderate to strong evidence suggests that exercise therapy and psychosocial interventions are effective for relieving pain and improving function for musculoskeletal pain. NSAIDs and opioids reduce pain in the short-term, but the effect size is modest and the potential for adverse effects need careful consideration. Corticosteroid injections were found to be beneficial for short-term pain relief among patients with knee and shoulder pain. However, current evidence remains equivocal on optimal dose, intensity and frequency, or mode of application for most treatment options. Conclusion This review presents a comprehensive summary and critical assessment of current evidence for the treatment of pain presentations in primary care. The evidence synthesis of interventions for common musculoskeletal pain presentations shows moderate-strong evidence for exercise therapy and psychosocial interventions, with short-term benefits only from pharmacological treatments. Future research into optimal dose and application of the most promising treatments is needed.